1H‐NMR Quantification of Major Saccharides in Açaí Raw Materials: a Comparison of the Internal Standard Methodology with the Absolute Intensity qNMR Method. Issue 6 (23rd May 2013) - Sterling, Cole; Crouch, Ronald; Russell, David J.; Calderón, Angela I.
ABSTRACT: Introduction: While the use of internal standard methodology for qNMR is a proven and reliable form of quantification, simplified alternative approaches are needed. Agilent's absolute intensity qNMR utility software is a valuable alternative that has not yet been subjected to validation in the peer‐reviewed literature. Objective: To provide validation of Agilent's absolute intensity qNMR method with a specific application to natural product quantification by measuring saccharide content in açaí materials. Methods: In order to validate the method, calibration test samples of ibuprofen were prepared in DMSO‐d6 at nine different concentrations and measured with 1 H‐NMR. A minimum of 40 spectra were collected for each sample, and the absolute intensity utility was used for quantification. The same methodology was then applied to the açaí materials, creating triplicates for each of the materials and using 3‐(trimethylsilyl)‐1‐propanesulphonic acid sodium salt in water‐d2 as both the solvent and internal standard. 1 H‐NMR spectra were collected, and the amounts of glucose, sucrose and fructose were determined using both the internal standard approach and the absolute intensity qNMR method. Results: Applying the absolute intensity utility to the ibuprofen samples demonstrated a linear response ( R 2  = 0.99943). For the açaí investigations, results obtained from the absolute intensity method were comparable to those obtained from the internal standard approach, with percentage differences ranging from 0.5–6.2%. Conclusion: This study demonstrates the accuracy, precision and reliability of Agilent's absolute intensity qNMR method. In addition, practical information is provided for assessing the saccharide contents of açaí materials. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this study, the validation of Agilent's absolute intensity qNMR utility is evaluated with ibuprofen, and its application is compared against the traditional internal standard approach by assessing differences in the major saccharide components of three types of açaí raw materials: organic, freeze‐dried non‐organic and processed non‐organic açaí powders. The comparable results generated from these two quantitative techniques indicated the accuracy, precision, and reliability of the absolute intensity qNMR utility as a tool for 1 H‐NMR quantification.